Turning to the visual turn: A review of some debates around Visual Studies and Philosophy of Image - Martínez Luna, Sergio (Eikón / Imago, 2024)
This article proposes a review of the theories of the image since the visual turn, both in the Anglo-Saxon context (W.J.T. Mitchell´s pictorial turn) and in the German context (Gottfried Boehm´s iconic turn). However, other perspectives are also considered, such as those coming from phenomenology (Emmanuel Alloa). The coincidences and differences between the two approaches are discussed, especially regarding how images produce meaning and their forms of action and agency. It also reviews the objections made to Visual Studies from disciplines such as History of Art. One of the key questions is that of the object of these studies, related to that of interdisciplinarity, as well as to the definition of the concept of visuality, which includes images and ways of seeing in their social and historical specificity. The debates between perceptualist and semiotic positions are linked to the conception of the image as appearance and mediation, presence, and representation. The article argues for maintaining the aporias and ambiguities of the image, for it is these that retain its critical potential, especially pressing in the age of machinic networked images and artificial vision.